고욤나무 열매의 영양성분 및 항산화 활성 - 신경옥(Kyung-Ok Shin); 양명(Ming Yang); 안수린(Soo Rin Ahn) (한국식품과학회지, 2022)
This study was conducted to determine whether Diospyros lotus L. fruit could be used as a natural functional food ingredient and whether its use should be increased. D. lotus fruit powder was found to have high acidity in the immature IDL stage and significantly higher sugar content in the mature MDL stage. The levels of crude fat, selenium, and tannins decreased significantly from the IDL stage to the MDL stage in D. lotus fruit powder. However, the levels of magnesium and calcium were significantly greater in the MDL stage than in the IDL stage (p<0.05). The total phenol content was significantly higher in the IDL stage, but the DPPH radical scavenging activity significantly increased in the MDL stage (p<0.05). In conclusion, the fruits of D. lotus. have high nutritional quality in both the immature and mature growth stages. Thus, it is a good candidate for use as a functional food, and its use should be increased because of its high nutritional qualities. 본 연구는 고욤나무 열매 분말의 활용도를 높여 천연 기능성 식품의 재료로써 사용이 가능한지를 영양학적으로 판단하기 위해 실시하였다. 고욤나무 열매 분말의 IDL 단계에서는 산도가 높았으며, MDL 단계에서는 당도가 유의하게 높았다(p<0.05). 조지방, 셀레늄 및 타닌 함량은 고욤나무 열매 분말의 IDL 단계에서 MDL 단계로 갈수록 유의적으로 감소하였으나, 마그네슘과 칼슘 함량의 경우 IDL 단계보다 MDL 단계에서 유의적으로 증가하였다(p<0.05). IDL 단계에서 총 페놀 함량이 유의적으로 높았으나, DPPH 라디칼 소거활성은 MDL 단계에서 유의하게 증가하였다(p<0.05). 아질산염 소거능과 타닌 함량은 IDL 단계에서 높았다. 본 연구를 종합해 볼 때, 고욤나무 열매는 각 성장 시기별로 영양학적 특성을 가지므로, 이를 고려하여 고욤나무 열매를 분말화하여 다양한 기능성 식품의 원료로서 활용한다면, 좋은 먹거리 제공 식품으로서 활용도를 높일 것으로 판단된다.